2007
DOI: 10.1007/s11568-006-9000-3
|View full text |Cite
|
Sign up to set email alerts
|

Searching for potential microRNA-binding site mutations amongst known disease-associated 3′ UTR variants

Abstract: The 3¢ untranslated regions (3¢ UTRs) of human protein-coding genes play a pivotal role in the regulation of mRNA 3¢ end formation, stability/degradation, nuclear export, subcellular localisation and translation, and hence are particularly rich in cis-acting regulatory elements. One recent addition to the already large repertoire of known cis-acting regulatory elements are the microRNA (miRNA) target sites that are present in the 3¢ UTRs of many human genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As previously reported, miRNAs modulated their biological functions through regulating target gene expression through complementarily binding to the 3′ UTR of mRNAs and miRNAs might play their roles by targeting multiple mRNAs (Chuzhanova et al, 2007). In the present report, using bioinformatic analysis, we showed that several genes were predicted to be potential targets of miR‐22, including SIRT1, NAT5, PTEN, HDAC4, and SRF.…”
Section: Discussionmentioning
confidence: 78%
“…As previously reported, miRNAs modulated their biological functions through regulating target gene expression through complementarily binding to the 3′ UTR of mRNAs and miRNAs might play their roles by targeting multiple mRNAs (Chuzhanova et al, 2007). In the present report, using bioinformatic analysis, we showed that several genes were predicted to be potential targets of miR‐22, including SIRT1, NAT5, PTEN, HDAC4, and SRF.…”
Section: Discussionmentioning
confidence: 78%
“…Generally, miRNAs modulate their biological functions through regulating target gene expression through complementarily binding to the 3′-UTR of mRNAs [28]. Each miRNA could repress possibly hundreds of transcripts, and there are interactions between miRNAs in the complex regulatory network of cardiac hypertrophy [29].…”
Section: Discussionmentioning
confidence: 99%